Recent Advances in Textile Composites - Proceedings of the 10th International Conference on Textile Composites: (TEXCOMP10) - Binetruy Christophe; Boussu François (DEStech Publications, 2010)
This book is an original and important collection of over 65 never previously published investigations in the fast-growing materials science field of textile composites. Chapters prepared for the book were presented initially at the tenth biennial TEXCOMP meeting, held in Lille, France, October 2010. The book includes new research on nanofibers, preforms, advanced braiding, multifunctional composites; useful design information and data for all phases of textile composites development; multiscale analysis, damage prediction, ballistics testing, mechanical design; and civil and military, structural and load-bearing applications. New work is presented in the subject areas of mechanical design, modeling, advanced manufacturing processes, characterization of preforms, nanofibers and composites, mechanical/thermal behavior, textile composites and impact, numerical methods and simulation, and natural fibers. This book will benefit scientists and engineers in the textile composites industry.